PEMBELAJARAN ILMU PENGETAHUAN SOSIAL TERPADU PADA SATUAN PENDIDIKAN MI/SD DAN MTs/SMP - Wahidmurni, Wahidmurni (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
The curriculum development from 1994 curricula to 2006 curricula has been called as KTSP or (kurikulum tingkat satuan pelajaran). As the consequence of the development, the structure of social science knowledge has been changed accordingly. In this sense, the teachers need to adopt teaching models in terms of planning, actuating and evaluating. In short, it is important for teachers, who teach social science, mastering to the concept, attitude and life-skill. As the impact, the students’ grades gradually increase.      Keywords:  Pembelajaran, IPS Terpadu